METHODOLOGY OF ORGANIZING INTERACTIVE GAMES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Tilavova Nargiza Turabovna (American Journals, 2023)
In our republic, a number of tasks related to the education of the mature generation are being implemented, and this process is preparing the ground for the education of young people with all-round developed intellectual potential. Formation of a mature generation is carried out first in the family, and then in the preschool educational organization. By the decision of the President of the Republic of Uzbekistan dated December 29, 2016 «On measures to further improve the preschool education system in 2017-2021» The program for 2021» was approved, and among the main objectives and directions of this program are to improve the quality of preschool education, to radically improve the quality of children’s preparation for school in preschool educational institutions, to introduce the educational process widely used in world practice. tasks of introducing modern educational programs and technologies are defined.